RELIGIOUS AND SOCIAL-PSYCHOLOGICAL FEATURES OF ADOPTING MANAGEMENT DECISIONS AMONG EXECUTIVES (American Journal of Research in Humanities and Social Sciences, 2024)
This article examines religious and socio-psychological factors that influence the process of making management decisions among executives. Various aspects, such as worldview, moral attitudes and influence group, as well as their significance for management effectiveness are analyzed.